A pausa na locução de poemas de Fernando Pessoa - Oh, Jae Keum (2010)
This project explores the issues of expressivity in speech by analyzing the nature of phonetic-acoustic and perceptive. The goal is to investigate the effects of pauses in the interpretation of four poems from the four main heteronyms of Fernando Pessoa by an announcer-actor. The object of this investigation is the relationship established between sound and meaning in this interpretation. The corpora are composed of a poem by each of the four main heteronyms Fernando Pessoa's Alberto Caeiro, Ricardo Reis, Álvaro de Campos and Fernando Pessoa by himself, recorded on CD. Acoustic Phonetic analysis includes the measurement of the pause using the software Praat. The results show the use of pauses by the speaker-actor according to the poetic text or backronym. The pauses in poetry reading have a role as developer of the architecture of oral interpretation or expression of meaning effects